A study on customers satisfactions towards services quality at the Store Soon Seng Plaza Melaka / Siti Fatimah Ibrahim - Ibrahim, Siti Fatimah (2013)
This research study is conducted at The Store Melaka. This study is on ‘Customers satisfaction towards Service Quality at The Store Melaka. The main objective of this study is to determine the level of customers satisfaction towards service quality provided at The Store Soon Seng Plaza with using five variables of SERVQUAL which are tangible, reliability, responsiveness, assurance and empathy as determinant. The researcher has adopted the descriptive research in order to conduct the research on the issue. The researcher’s sampling design is the Non probability sampling which is the Convenience Sampling Technique and 100 questionnaires were distributed to the customers of The Store Melaka which refers to the local and international target population of the research. The questionnaire was distributed to customers when purchasing at The Store Melaka. The researcher adopts Scientific Program of Social Science (SPSS) application to analyze the data that is gathered throughout the research process in order to obtain accurate answer for the questions. Based on findings, the researcher see that the customers moderate satisfied with Service Quality at The Store Melaka.